High-Flow Nasal Oxygen Therapy in Immunocompromised Patients With Acute Hypoxemic Respiratory Failure. Issue 4 (July 2018) - Decavèle, Maxens; Pousset, François; Faure, Morgane; Marois, Clémence; Mokart, Djamel; Lemiale, Virginie; Azoulay, Elie; Demoule, Alexandre
Abstract : Acute respiratory failure (ARF) is common in immunocompromised patients. Low/intermediate-flow oxygen devices have several drawbacks, such as insufficient humidification and warming of the inspired gas or limited FiO2, which imply suboptimal therapeutic management. Compared with unselected patients, immunocompromised patients are at higher risk of ARF, and ARF is associated with a 2-fold increase in intensive care unit or hospital mortality. As a consequence, decreasing the need for intubation by the improvement of oxygenation and ventilation techniques has become a major goal of care in this population. Besides noninvasive ventilation, high-flow therapy (HFT), which can deliver up to 60 to 70 L/min of an FiO2 controlled, heated and humidified oxygen, seems to be a promising alternative. Various mechanisms explain the benefit of HFT, including dead space washout, reduction in oxygen dilution, and nasopharyngeal resistance, more reliable FiO2 delivering, moderate positive end-expiratory pressure effect that may generate alveolar recruitment, and reduction of the work of breathing. To date, the retrospective and prospective studies conducted in immunocompromised patients suggest that HFT is well tolerated, alleviates symptoms of respiratory distress, and improves oxygenation. In addition, it might be associated with a reduction in intubation and mortality when compared with noninvasive ventilation. Finally, HFT seems to be a safe alternative to noninvasive ventilation to prevent respiratory symptoms and subsequent intubation during fiberoptic bronchoscopy and bronchoalveolar lavage. These promising benefits of HFT in immunocompromised patients need to be confirmed by large prospective randomized controlled trials performed specifically in immunocompromised patients.